Tax Education and Tax Knowledge on the Level of Land and Building Tax (PBB) Payment - Rainarius Juma; Aloisius Hama (CV Edujavare Publishing, 2026)
Land and Building Tax (PBB) is a crucial element in the regional revenue structure, playing a vital role in financing various infrastructure and public facility development projects in the region. Land and Building Tax revenue in Manggarai Regency has so far not reached the maximum target, indicating obstacles to public compliance in fulfilling their tax obligations. This study aims to conduct an empirical analysis of the role of tax education and understanding in influencing the intensity of PBB payments. This study employed a quantitative design through a survey technique aimed at PBB taxpayers in Manggarai Regency. The data collection instrument used was a structured questionnaire, which was then processed using a multiple linear regression model. The research findings indicate that tax education plays a significant role in constructing public attitudes and awareness, while tax literacy plays a significant role in strengthening technical understanding regarding regulations and procedures for fulfilling fiscal obligations. Simultaneously, both variables have been shown to have a positive influence on PBB payment rates. These findings indicate that improving the quality of tax education and understanding is an important strategy for local governments to encourage sustainable tax compliance.